Winding core and preparation method thereof, winding type solid-state battery
By adding block polymers with different component contents in the flat area and winding area of the solid electrolyte membrane, the problem of the solid electrolyte layer being easily broken in the winding part and causing short circuits in the battery are solved, and the battery flexibility and The effect of cycle performance.
Patent Information
- Application Number
- CN202411603926.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The solid electrolyte layer is prone to rupture in the winding part, resulting in a short circuit inside the battery.
In the flat area and winding area of the solid electrolyte membrane, block polymers with different component contents are added separately in the area. A accounts for more than 40% of the total mass of the block polymer in the flat area, and A accounts for 20 in the winding area. %~34% to improve the flexibility and ion conduction properties of the film.
By improving the flexibility of the solid electrolyte membrane, the risk of short circuits within the battery is reduced, and the cycling performance of the battery is improved.
Smart Images

Figure CN119133634B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a winding core and a preparation method thereof, and a wound solid-state battery. Background Art
[0002] Lamination and winding are two commonly used battery cell forming processes. However, since the solid electrolyte itself is not flexible and there is almost no adhesion between the solid electrolytes, the solid electrolyte layer is prone to rupture in the winding part. When the solid electrolyte layer ruptures, the positive and negative electrodes come into contact with each other, causing a short circuit inside the battery. Summary of the invention
[0003] Based on this, the present application provides a winding core and a preparation method thereof, and a wound solid-state battery to solve the above-mentioned technical problems.
[0004] The first aspect of the present application provides a winding core, comprising a positive electrode sheet, a negative electrode sheet, and a solid electrolyte membrane between the positive electrode sheet and the negative electrode sheet, wherein the solid electrolyte membrane comprises a flat region and a winding region, and both the flat region and the winding region comprise a solid electrolyte and a binder; wherein,
[0005] The binder comprises a block polymer of A and B, wherein A is a compound having a structure of formula (I), and B is a compound having a structure of formula (II).
[0006] ,
[0007] Wherein, R1~R3 and R1'~R6' are each independently selected from hydrogen or an alkyl group;
[0008] In the plateau region, A accounts for more than 40% of the total mass of the block polymer;
[0009] In the coiled region, A accounts for 20% to 34% of the total mass of the block polymer.
[0010] In some embodiments, the mass percentage of the binder in the solid electrolyte membrane is 0.5% to 5%.
[0011] In some embodiments, the solid electrolyte membrane has a thickness of 10 μm to 100 μm.
[0012] In some embodiments, the winding region includes the entire curved area of the solid electrolyte membrane.
[0013] In some embodiments, in the winding region from the inner layer of the core to the outer layer of the core, the mass percentage of A in the block polymer increases sequentially.
[0014] In some embodiments, in the solid electrolyte membrane located at the innermost layer of the core, A in the winding region accounts for 20% to 25% of the total mass of the block polymer.
[0015] In some embodiments, the winding zone includes a bending zone and a transition zone, and the mass percentage of A in the transition zone to the block polymer is less than the mass percentage of A in the bending zone to the block polymer; wherein the transition zone connects the flat zone and the bending zone.
[0016] In some embodiments, in the transition region, A accounts for 20% to 25% of the total mass of the block polymer.
[0017] In some embodiments, the solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a hydride solid electrolyte, a boride solid electrolyte, a nitride solid electrolyte, and a polymer solid electrolyte.
[0018] The second aspect of the present application provides a method for preparing a core as provided in the first aspect, comprising the following steps:
[0019] Mixing a solid electrolyte, a binder and a solvent to prepare a slurry;
[0020] Applying the slurry on the surface of the first pole piece;
[0021] Drying to form a solid electrolyte membrane on the surface of the first electrode; compounding the second electrode on the surface of the solid electrolyte membrane to obtain a laminate;
[0022] Winding the laminate to form a winding core;
[0023] The step of mixing the solid electrolyte, the binder and the solvent comprises: adjusting the mass percentage of A in the binder to the block polymer.
[0024] The third aspect of the present application provides a wound solid-state battery, comprising the core provided by the first aspect or the core prepared according to the preparation method provided by the second aspect.
[0025] In the present application, block polymers including A and B with different component contents are added to the flat area and the winding area of the solid electrolyte membrane in different regions. In the winding area, A accounts for 20% to 34% of the total mass of the block polymer, so that the solid electrolyte membrane has excellent flexibility and the battery is not prone to internal short circuit. At the same time, in the flat area, A accounts for more than 40% of the total mass of the block polymer, so that the battery has good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of a winding core in one embodiment of the present application.
[0027] Figure 2 Schematic diagram of a winding core in one embodiment of the present application.
[0028] Figure 3 1 is a process flow chart of a method for preparing a winding core in one embodiment of the present application.
[0029] Description of Reference Numerals
[0030] 1. Winding area; 2. Flat area;
[0031] 11. Bending zone; 12. Transition zone. DETAILED DESCRIPTION
[0032] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0033] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0034] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0036] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100~150 nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, mentioning that the method may also include step (c) means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0041] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0042] like Figure 1-2 As shown, the first aspect of the present application provides a winding core, which includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte membrane between the positive electrode sheet and the negative electrode sheet. The solid electrolyte membrane includes a flat area 2 and a winding area 1, and the flat area 2 and the winding area 1 both include a solid electrolyte and a binder.
[0043] The binder comprises a block polymer of A and B, wherein A is a compound having a structure of the following formula (I), and B is a compound having a structure of the following formula (II).
[0044] ,
[0045] Wherein, R1 to R3 in formula (I) and R1′ to R6′ in formula (II) are each independently selected from hydrogen or an alkyl group.
[0046] In plateau 2, A accounts for more than 40% of the total mass of the block polymer, including but not limited to 40%, 41%, 42%, 45%, 46%, 48%, and 50%.
[0047] In winding zone 1, A accounts for 20% to 34% of the total mass of the block polymer, including but not limited to 20%, 21%, 22%, 23%, 24%, 26%, 28%, 30%, 32%, and 34%.
[0048] In the present application, block polymers including A and B with different component contents are added to the flat area 2 and the winding area 1 of the solid electrolyte membrane in different regions. In the winding area, A accounts for 20% to 34% of the total mass of the block polymer. The block polymer has good elasticity and elongation properties, so that the winding area of the solid electrolyte membrane has excellent flexibility and improved anti-rupture performance, thereby reducing the risk of internal short circuit of the battery. In the flat area, A accounts for more than 40% of the total mass of the block polymer. The increase in conjugated structure makes the block polymer have better ion conductivity, thereby making the battery have better cycle performance.
[0049] In some embodiments, the mass percentage of the binder in the solid electrolyte membrane is 0.5% to 5%, including but not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.
[0050] In some embodiments, the solid electrolyte membrane has a thickness of 10 μm to 100 μm, including but not limited to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm.
[0051] In some embodiments, the winding region 1 in the solid electrolyte membrane includes the entire curved region of the solid electrolyte membrane.
[0052] Preferably, the winding area 1 in the solid electrolyte membrane is the entire bending area of the solid electrolyte membrane.
[0053] In some embodiments, in the winding zone 1 from the inner layer of the core to the outer layer of the core, the mass percentage of A in the block polymer increases successively.
[0054] The winding radius of the winding area 1 close to the inside of the core is smaller, and the flexibility requirements for the solid electrolyte membrane are higher. Therefore, by setting the mass percentage of A in the winding area 1 inside the core to be lower, and setting the mass percentage of A in the block polymer in the winding area from the inner layer of the core to the outer layer of the core to increase successively, not only the possibility of breakage of the solid electrolyte membrane in the winding area 1 in each layer of the core can be reduced, but also the ion conductivity performance of the entire solid electrolyte membrane can be improved.
[0055] In some embodiments, in the solid electrolyte membrane located in the innermost layer of the core, that is, in the winding area 1 of the first solid electrolyte membrane, A accounts for 20% to 25% of the total mass of the block polymer, including but not limited to 20%, 21%, 22%, 23%, 24%, and 25%.
[0056] In some embodiments, in transition zone 12, A accounts for 20% to 25% of the total mass of the block polymer, including but not limited to 20%, 21%, 22%, 23%, 24%, and 25%.
[0057] The present application provides a higher flexibility for the solid electrolyte membrane by setting a lower mass proportion of A in the block polymer of the transition zone 12 relative to the bending zone 11 and the flat zone 2 in the binder of the transition zone 12, thereby effectively resisting stress deformation and / or stress concentration that may occur in the transition zone 12, and further improving the anti-fragmentation performance of the solid electrolyte membrane.
[0058] The present application does not specifically limit the type of solid electrolyte. Under the premise of satisfying the overall inventive concept of the present application, any known type of solid electrolyte can be used in the present application. It is only used as an illustrative example rather than a limitation on the scope of protection. The solid electrolyte includes one or more of oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, hydride solid electrolytes, boride solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.
[0059] Specifically, the oxide solid electrolyte is composed of oxide solid electrolyte particles, and may include one or more garnet ceramics, LISICON type oxides, NASICON type oxides, and perovskite type ceramics. For example, one or more garnet ceramics may be selected from the group consisting of: Li 6.5 Ln3Z 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O12 , Li 6.75 La3Zr 1.75 Nb 0.25 O 12 and combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li14Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. One or more NASICON-type oxides may be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example: In certain variations, one or more NASICON-type oxides may be selected from the group consisting of: Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1. 7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. One or more perovskite-type ceramics may be selected from the group consisting of: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1. 3Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) and combinations thereof. In one variation, one or more oxide-based materials may have a value greater than or equal to about 10-5 S / cm to less than or equal to about 10 -1 S / cm ionic conductivity.
[0060] The sulfide solid electrolyte is composed of sulfide solid electrolyte particles and may include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 , Li 10 SiP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 、(1-x)P2S 5-x Li2S (where 0.5≤x≤0.7) and combinations thereof. In one variation, one or more sulfide-based materials may have a carbon content greater than or equal to about 10 -7 S / cm to an ionic conductivity of less than or equal to about 1 S / cm.
[0061] The halide solid electrolyte can be composed of halide solid electrolyte particles, including Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1) and combinations thereof. In one variant, one or more halide-based materials can have an ionic conductivity greater than or equal to about 10 -8 S / cm to less than or equal to about 10 -1 S / cm.
[0062] The hydride solid electrolyte is composed of hydride solid electrolyte particles, and the hydride-based particles can include one or more hydride-based materials selected from the group consisting of: Li3AlH6, LiBH4, LiBH4-Li X (where X is one of Cl, Br, and I), LiNH2, Li2NH, LiBH4-LiNH2, and combinations thereof. In one variant, one or more hydride-based materials can have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm.
[0063] The boride solid electrolyte is composed of borate solid electrolyte particles, including one or more borate-based materials from the group consisting of: Li2B4O7, Li2O-(B2O3)-(P2O5), and combinations thereof. In one variant, one or more borate-based materials can have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm.
[0064] The nitride solid electrolyte is composed of nitride solid electrolyte particles, including Li3N, Li7PN4, LiSi2N3, LiPON, and combinations thereof. In one variant, one or more nitride-based materials can have an ionic conductivity greater than or equal to about 10 -9 S / cm to less than or equal to about 1 S / cm.
[0065] The components of the polymer solid electrolyte may include one or more polymer materials selected from the group consisting of polyethylene glycol, polyethylene oxide (PEO), poly(p-phenylene oxide) (PPO), poly(methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride co-hexafluoropropylene (PVDF-HFP), polyvinyl chloride (PVC), and combinations thereof. In one variation, the one or more polymer materials may have a molecular weight equal to about 10 -4 S / cm ionic conductivity.
[0066] In the present application, there is no particular limitation on the positive electrode sheet, as long as it can function as the positive electrode of the all-solid-state battery, as long as it conforms to the overall inventive concept of the present application. The following is only exemplary, and the positive electrode includes a positive electrode current collector, a positive electrode active material, a conductive agent, and a binder.
[0067] In some embodiments, the positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. Specifically, copper, stainless steel, aluminum, nickel, titanium, or a metal current collector with a surface treated with carbon or other substances can be used.
[0068] In some embodiments, the positive electrode active material is one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganate, lithium nickel cobalt aluminum oxide, lithium-rich manganese base, elemental sulfur, sodium iron manganate, sodium iron titanate, sodium iron sulfate, sodium iron phosphate, sodium vanadium phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, and lithium titanate materials.
[0069] In the present application, there is no particular limitation on the negative electrode sheet, as long as it can function as the negative electrode of the all-solid-state battery under the premise of conforming to the overall inventive concept of the present application. The following is only for illustrative purposes, and the negative electrode includes a negative electrode current collector, a negative electrode active material, a conductive agent, and a binder.
[0070] In some embodiments, the shape of the negative electrode collector includes any one of a foil shape, a plate shape or a grid shape; further, the negative electrode collector includes any one of aluminum, copper, nickel or zinc; optionally, the negative electrode collector is a copper element, such as copper foil, etc.; further, the negative electrode collector includes any one of aluminum, copper, nickel or zinc alloy.
[0071] In some embodiments, the negative electrode active material is one or more of graphite, silicon, silicon oxygen, silicon carbon, lithium titanate, hard carbon, soft carbon, tin oxide, and titanium dioxide.
[0072] In some embodiments, the conductive agent includes, but is not limited to, carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include, for example, particles of carbon black, graphite, super-P, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate, and the like.
[0073] In some embodiments, the binder includes, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polycarbonate (PC), polyamide (PA), acrylic plastics, other polyolefins and copolymers thereof, polysulfone, polyphenylene oxide (PPO) and carboxymethyl cellulose (CMC). Further, the binder is polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF).
[0074] like Figure 3 As shown, the second aspect of the present application provides a method for preparing a core as provided in the first aspect, comprising the following steps:
[0075] Mixing a solid electrolyte, a binder and a solvent to prepare a slurry;
[0076] Applying the slurry on the surface of the first pole piece;
[0077] Drying to form a solid electrolyte membrane on the surface of the first electrode; compounding the second electrode on the surface of the solid electrolyte membrane to obtain a laminate;
[0078] Winding the laminate to form a winding core;
[0079] The step of mixing the solid electrolyte, the binder and the solvent comprises: adjusting the mass percentage of A in the binder to the block polymer.
[0080] For ease of explanation, in this application, a binder containing a block polymer with an A mass percentage of 40% or more is referred to as a high-ratio binder, and a binder containing a block polymer with an A mass percentage of 20% to 34% is referred to as a low-ratio binder.
[0081] Specifically, adjusting the mass percentage of A in the block polymer includes: increasing the supply of a high-proportion binder along the coating direction of the first electrode while reducing (or stopping) the supply of a low-proportion binder; or, increasing the supply of a low-proportion binder while reducing (or stopping) the supply of a high-proportion binder; thereby forming a solid electrolyte coating in which the first coating area and the second coating area are arranged at intervals in the coating direction, and the first coating area contains a high-proportion binder, and the second coating area contains a low-proportion binder; therefore, in the core prepared in the present application, in the flat area of the solid electrolyte membrane, A accounts for more than 40% of the total mass of the block polymer, and in the winding area of the solid electrolyte membrane, A accounts for 20%~34% of the total mass of the block polymer.
[0082] Further, adjusting the mass percentage of A in the block polymer may include: adjusting the mass percentage of A in the low-ratio binder in the slurry used to form the second coating area in sequence along the coating direction of the first pole piece, so that in the obtained winding core, the mass percentage of A in the winding area 1 from the inner layer of the winding core to the outer layer of the winding core increases in sequence.
[0083] The winding radius of the winding area 1 close to the inside of the core is smaller, and the flexibility requirements for the solid electrolyte membrane are higher. Therefore, by setting the mass percentage of A in the winding area 1 inside the core to be lower, and setting the mass percentage of A in the block polymer in the winding area from the inner layer of the core to the outer layer of the core to increase successively, not only the possibility of breakage of the solid electrolyte membrane in the winding area 1 in each layer of the core can be reduced, but also the ion conductivity performance of the entire solid electrolyte membrane can be improved.
[0084] In some of the embodiments, the slurry is coated on the surface of the electrode plate by a coating machine, and the final coating thickness can be controlled by adjusting the concentration of the slurry solution and / or the number of coatings.
[0085] It is understood that the above-mentioned drying treatment step is a process for removing solvent and water from the slurry for drying the slurry coated on the electrode plate, which can be adjusted according to the different solvents used. For example, it is carried out in a vacuum oven at 50°C to 200°C. Drying methods include, for example, drying by warm air, hot air, low-humidity air, vacuum drying or irradiation with (far) infrared or electromagnetic radiation. The drying time is not particularly limited and is usually 30s to 24h.
[0086] In some embodiments, the first electrode sheet is one of a positive electrode sheet and a negative electrode sheet, and the second electrode sheet is the other one of them.
[0087] In some embodiments, the method for preparing the core further comprises the following steps:
[0088] preparing a positive electrode sheet;
[0089] Prepare the negative electrode sheet.
[0090] It is understandable that in the present application, there is no particular limitation on the preparation method of the positive electrode sheet and the negative electrode sheet, and they can be easily manufactured by known methods under the premise of complying with the overall inventive concept of the present application.
[0091] In some embodiments, preparing the positive electrode sheet comprises the following steps:
[0092] The positive electrode active material, the binder and the conductive agent are mixed and added into a solvent to prepare a positive electrode slurry;
[0093] The positive electrode slurry is coated on the positive electrode current collector, and after drying and roll pressing, a positive electrode sheet is obtained.
[0094] In some embodiments, preparing the negative electrode sheet comprises the following steps:
[0095] The negative electrode active material, the binder and the conductive agent are mixed and added into a solvent to prepare a negative electrode slurry;
[0096] The negative electrode slurry is coated on the negative electrode current collector, and after drying and roll pressing, a negative electrode sheet is obtained.
[0097] It is understandable that the present application does not specifically limit the type of solvent. Under the premise of satisfying the inventive concept of the present application, any known type of solvent can be applied to the present application. The following are merely illustrative examples rather than limitations on the scope of protection. For example, the solvent may be N-methylformamide (NMF).
[0098] The third aspect of the present application provides a wound solid-state battery, comprising the core provided by the first aspect or the core prepared according to the preparation method provided by the second aspect.
[0099] In the present application, there is no particular limitation on the preparation process of the wound solid-state battery. Any known process method for preparing a wound solid-state battery can be used as long as the overall inventive concept of the present application is met.
[0100] The present application will be further described below with reference to specific embodiments and comparative examples.
[0101] In the following, preferred embodiments are given to facilitate understanding of the present invention, but it is obvious to those skilled in the art that the following embodiments are merely examples of the present invention, and various changes and modifications can be made within the scope of the present invention and technical ideas, and such changes and modifications fall within the scope of the appended patent claims.
[0102] Example 1
[0103] Preparation of positive electrode:
[0104] The positive electrode active material lithium manganese oxide, the binder PVDF, and the conductive agent Super-P are weighed in a mass ratio of 95:3:2, and mixed evenly by a jet mill, and the solvent NMP is added to form a uniform slurry. The slurry is coated on the surface of the aluminum foil current collector, dried, and pressed to form a positive electrode sheet.
[0105] Preparation of negative electrode sheet:
[0106] The negative electrode active material graphite, the binder PVDF, and the conductive agent Super-P were weighed in a mass ratio of 95:3:2, and mixed evenly by a jet mill, and the solvent NMP was added to form a uniform slurry. The slurry was coated on the surface of the copper foil current collector, dried, and pressed to form a negative electrode sheet.
[0107] Preparation of solid electrolyte membrane:
[0108] The solid electrolyte lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 The slurry of (PO4)3, LATP) and the binder solution is supplied to a kneader, and then the slurry is coated on the surface of the positive electrode sheet by a coater; and a solid electrolyte membrane is formed on the surface of the positive electrode sheet after drying.
[0109] The binder is a block polymer of A and B, wherein A is a compound having a structure of the following formula (III), and B is a compound having a structure of the following formula (IV). The thickness of the solid electrolyte membrane is 30 μm.
[0110] , ,
[0111] Prepare a winding core (taking the example that the number of winding areas from the inner layer of the winding core to the outer layer of the winding core is equal to 5).
[0112] The negative electrode sheet is compounded on the surface of the solid electrolyte membrane to obtain a laminate, and the laminate is wound to form a winding core.
[0113] The mass percentage of the binder in all solid electrolyte membranes is 2%. In addition, A accounts for 40% of the total mass of the block polymer in the flat area of the solid electrolyte membrane, and A accounts for 22% of the total mass of the block polymer in the winding area.
[0114] Example 2
[0115] The difference between this embodiment and embodiment 1 is that A in the flat region of the solid electrolyte membrane accounts for 41% of the total mass of the block polymer, and A in the coiled region accounts for 34% of the total mass of the block polymer.
[0116] Example 3
[0117] The difference between this embodiment and embodiment 1 is that A in the winding region accounts for 32% of the total mass of the block polymer.
[0118] Example 4
[0119] The difference between this embodiment and embodiment 1 is that A in the winding region accounts for 20% of the total mass of the block polymer.
[0120] Example 5
[0121] The difference between this embodiment and embodiment 1 is that the mass percentage of the binder in all solid electrolyte membranes is 0.5%.
[0122] Example 6
[0123] The difference between this embodiment and embodiment 1 is that the mass percentage of the binder in all solid electrolyte membranes is 5%.
[0124] Example 7
[0125] The difference between this embodiment and embodiment 1 is that the thickness of the solid electrolyte membrane is 10 μm.
[0126] Example 8
[0127] The difference between this embodiment and embodiment 1 is that the thickness of the solid electrolyte membrane is 100 μm.
[0128] Example 9
[0129] The difference between this embodiment and embodiment 1 is that the content of A in the block polymer in the winding area from the inner layer of the core to the outer layer of the core is 20%, 24%, 28%, 30% and 32% respectively.
[0130] Example 10
[0131] The difference between this embodiment and embodiment 1 is that the content of A in the block polymer in the transition zone 12 in the winding zone is 22%, and the content of A in the block polymer in the bending zone 11 is 34%.
[0132] Embodiment 11
[0133] The difference between this embodiment and embodiment 1 is that B is a compound having the structure of the following formula (V).
[0134]
[0135] Example 12
[0136] The difference between this embodiment and embodiment 1 is that A is a compound having the following structure:
[0137]
[0138] Example 13
[0139] The difference between this embodiment and embodiment 1 is that A in the flat area of the solid electrolyte membrane accounts for 41% of the total mass of the block polymer, A in the winding area accounts for 34% of the total mass of the block polymer, the mass percentage of the binder in the solid electrolyte membrane is 8%, and the thickness of the solid electrolyte membrane is 105μm.
[0140] Comparative Example 1
[0141] The difference between this comparative example and Example 1 is that A in the winding area of the solid electrolyte membrane accounts for 36% of the total mass of the block polymer.
[0142] Comparative Example 2
[0143] The difference between this comparative example and Example 1 is that A in the flat region of the solid electrolyte membrane accounts for 35% of the total mass of the block polymer, and A in the wound region of the solid electrolyte membrane accounts for 32% of the total mass of the block polymer.
[0144] The test parameters of the embodiments and comparative examples are summarized in Table 1 below.
[0145] Preparation of wound solid-state batteries:
[0146] The solid electrolyte membrane prepared according to the above-mentioned embodiment and proportion is used to prepare a wound solid-state battery.
[0147] Test Case
[0148] (1) Cyclic performance tests were performed on batteries prepared using the solid electrolyte membranes prepared in the above examples and comparative examples:
[0149] Temperature: 25℃±2℃
[0150] ① Charge at 1C or specified current to the end voltage, cut-off current 0.05C, and let stand for 30 minutes;
[0151] ② Discharge at 1C to the final discharge voltage (2.75V), record the discharge capacity, and let stand for 30 minutes;
[0152] Loop ①~②
[0153] The lithium-ion battery was cycled 500 times according to the above method, and the discharge capacity of the 100th cycle was detected. The capacity retention rate (%) of the lithium-ion battery after 500 cycles was calculated as (discharge capacity of the lithium-ion battery after 500 cycles / discharge capacity of the lithium-ion battery in the first cycle) × 100%. The calculation results are shown in Table 1 below.
[0154] (2) Flexibility testing
[0155] After the positive electrode sheet and the negative electrode sheet with the solid electrolyte membrane formed in the above-mentioned embodiment and comparative example are bonded together, 4t / cm2 The laminate was obtained by pressing, and the obtained laminate was wound to obtain a wound-type all-solid-state battery. The presence of cracks was observed. The results are shown in Table 1 below.
[0156] Table 1
[0157]
[0158] By comparing the embodiment with comparative example 1, it can be seen that when the content (%) of A in the winding zone block polymer exceeds 34%, the flexibility of the solid electrolyte membrane decreases, cracking is easily generated, and short circuit is easily caused inside the battery.
[0159] By comparing the embodiment with comparative example 2, it can be seen that when the content (%) of A in the flat region block polymer is lower than 40%, the cycle performance of the solid electrolyte membrane decreases.
[0160] The technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0161] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A winding core, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane between the positive electrode sheet and the negative electrode sheet, the solid electrolyte membrane includes a flat area and a winding area, and the flat area and the winding area both include a solid electrolyte and a binder; wherein, The binder comprises a block polymer of A and B, wherein A is a compound having a structure of formula (I), and B is a compound having a structure of formula (II). 、 , Wherein, R1~R3 and R1'~R6' are each independently selected from hydrogen or an alkyl group; In the flat region, the A accounts for more than 40% of the total mass of the block polymer; In the winding region, the A accounts for 20% to 34% of the total mass of the block polymer.
2. The winding core according to claim 1, characterized in that: The mass percentage of the binder in the solid electrolyte membrane is 0.5% to 5%.
3. The winding core according to claim 1, characterized in that: The thickness of the solid electrolyte membrane is 10 μm to 100 μm.
4. The winding core according to claim 1, characterized in that: The winding region includes the entire curved area of the solid electrolyte membrane.
5. The winding core according to claim 1, characterized in that: In the winding region from the inner layer of the core to the outer layer of the core, the mass percentage of A in the block polymer increases successively.
6. The winding core according to claim 5, characterized in that: In the solid electrolyte membrane located in the innermost layer of the winding core, A in the winding area accounts for 20% to 25% of the total mass of the block polymer.
7. The winding core according to claim 1, characterized in that: The winding zone includes a bending zone and a transition zone, and the mass percentage of A in the transition zone to the block polymer is less than the mass percentage of A in the bending zone to the block polymer; wherein the transition zone connects the flat zone and the bending zone.
8. The winding core according to claim 7, characterized in that: In the transition zone, A accounts for 20% to 25% of the total mass of the block polymer.
9. A method for preparing a winding core according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mixing a solid electrolyte, a binder and a solvent to prepare a slurry; Applying the slurry on the surface of the first pole piece; Drying to form a solid electrolyte film on the surface of the first electrode; Compounding the second pole piece on the surface of the solid electrolyte membrane to obtain a laminate; Winding the laminate to form a winding core; The step of mixing the solid electrolyte, the binder and the solvent comprises: adjusting the mass percentage of A in the binder to the block polymer; The first pole piece and the second pole piece are independently selected from a positive pole piece and a negative pole piece, respectively, and the first pole piece and the second pole piece are different.
10. A wound solid-state battery, characterized in that: A core comprising the core according to any one of claims 1 to 8 or a core prepared according to the method for preparing the core according to claim 9.
Citation Information
Patent Citations
Winding type all solid state battery
JP2015103433A